2019
DOI: 10.5194/isprs-archives-xlii-4-w18-235-2019
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Aerosol Form Clouds Using Cats-Iss Lidar Observations Based on Random Forest and SVM Algorithms Over the Eastern Part of Middle East

Abstract: Abstract. Aerosols and Clouds play an important role in the Earth's environment, climate change and climate models. The Cloud-Aerosol Transport System (CATS) as a lidar remote sensing instrument, from the International Space Station (ISS), provides range-resolved profile measurements of atmospheric aerosols and clouds. Discrimination aerosols from clouds have always been a challenges task in the classification of space-born lidars. In this study, two algorithms including Random Forest (RF) and Support Vector M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…RF was also used for lidar measurements specifically. Brakhasi et al [17] used two algorithms, including RF, to discriminate aerosols from clouds in satellite-based lidar measurements, and they found the method had higher accuracy compared to probability distribution function-based algorithms. Liu et al [24] compared several machine learning algorithms on air pollution (SO 2 and NO 2 ) classification and found that RF can give a good result.…”
Section: Machine Learning Algorithmsmentioning
confidence: 99%
“…RF was also used for lidar measurements specifically. Brakhasi et al [17] used two algorithms, including RF, to discriminate aerosols from clouds in satellite-based lidar measurements, and they found the method had higher accuracy compared to probability distribution function-based algorithms. Liu et al [24] compared several machine learning algorithms on air pollution (SO 2 and NO 2 ) classification and found that RF can give a good result.…”
Section: Machine Learning Algorithmsmentioning
confidence: 99%